THE EFFECT OF RELIGIOSITY AND BOYCOTT DECISIONS ON BRAND LOYALTY OF PRO-ISRAEL PRODUCTS - Sugeng Nugroho Hadi; Khadijah Syafira Adyani (Magister Manajemen Universitas Islam Malang, 2025)
AbstractThe boycott action against pro-Israel products is widely voiced by Muslim consumers as a form of concern for Muslims in Gaza, Palestine, who have been unjustly massacred for years, triggering genocide by the Israeli Zionists. This study aims to determine the influence of religiosity and brand loyalty on the action of Muslim boycott decisions against pro-Israel products. From this objective, a research question can be developed,